CAN RAPID TROPONIN T BE USED AS A SINGLE RELIABLE TEST IN THE DIAGNOSIS OF ACUTE MYOCARDIAL INFARCTION? - Fareeda J; Waseem A; Nasreen G; Javed S (Asian Journal of Medicine & Health Sciences, 2019)
Introduction: Myocardial infarction (MI), a common cause of mortality and morbidity, needs early and reliable diagnosis. We determined the validity of rapid troponin T (rTropT) in the diagnosis of MI in our local population to know if it can be used as a single diagnostic test. Method: This was a case control study conducted in patients admitted to ICU/CCU/medical ward in a teaching hospital towards north of Pakistan over a period of six months. Fifty patients were included in study group and 50 in control group, depending on the presence or absence of MI respectively. Patients in control group were age and sex matched. WHO criteria was used for the diagnosis of acute MI. Rapid TropT was performed in study group after establishing the diagnosis of MI and in control group after excluding the diagnosis of acute MI. CK, SGOT, LDH and rTropT were done by Humazyn M test kit Germany, Granutest Merck Germany, monokinetic method and Boehringer Mannheim Germany respectively. Results: In the study group, 34 (68%) patients were male. Age range was 55-65 years. Overall sensitivity, specificity, positive predictive value and negative predictive value of Rapid troponin T were 92% (CI 80.8-97.8), 100% (CI 92.89-100.0), 100% and 92.6% (CI 83.0-96.9) respectively. Conclusion. Rapid trop T was a reliable marker for the diagnosis of MI in our patients over a prolonged window period of 7 days after MI. So it can be used as a single diagnostic test in our local population avoiding the need to do many other tests.